2018
DOI: 10.21767/2577-0594.100012
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling of Wet Rice Straw using Biogas Slurry and Molasses in Monsoon of Bangladesh

Abstract: This paper presents an experiment of the preparation of ensilage with wet rice straw (WRS) treated with biogas slurry (BGS) and ensiled with molasses to increase the nutritional and preservation quality of straw in monsoon season of Bangladesh in the Department of Animal Science, Bangladesh Agricultural University (BAU), Mymensingh. Chopped wet straw was preserved in plastic containers under airtight condition at room temperature based on the treatments as T 0 (100% WRS only), T 1 (0% BGS), T 2 (5% BGS), T 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…DM was decreased from 22.58 to 20.83% (Otieno et al, 1986) and from 29.1 to 26.5% (Hiep and Man 2003) in ensiled maize stover. It was observed that DM content was decreased with the ensiling time from 31.76 to 27.37%with the increase of duration from 0 to 90 days (Sarker et al, 2018). Losses of DM may come from run off, oxidation and loss of volatile organic compounds (Kung 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM was decreased from 22.58 to 20.83% (Otieno et al, 1986) and from 29.1 to 26.5% (Hiep and Man 2003) in ensiled maize stover. It was observed that DM content was decreased with the ensiling time from 31.76 to 27.37%with the increase of duration from 0 to 90 days (Sarker et al, 2018). Losses of DM may come from run off, oxidation and loss of volatile organic compounds (Kung 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It helps in facilitating the natural preservation by lowering the pH and producing lactic acid bacteria (Premiar, 2006). It increases the palatability and also digestibility of rice straw (Sarker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Solid and liquid wastes release nitrate and phosphate to the soil and water streams, as well as carbon di oxide, methane, ammonia, hydrogen sulphide, di & tri methyl sulphide gases are released to the air during aerobic and anaerobic decomposition (Ahsan et al, 2014;Lee et al, 2009;Won et al, 2016) due to inappropriate treatment of wastes Sarker et al, 2009;Roy et al, 2013). Cattle manure is a valuable resource as a soil fertilizer, as it provides high contents of macro and micro-nutrients for crop growth and is a low-cost alternative to mineral fertilizers (Ghos et al, 2004;Islam et al, 2010;Rahman et al, 2008;Sarker et al, 2018). Composting and vermicomposting are two well known processes for the utilization of manures that produced composts and vermicompost.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock is one of the most important components of agriculture that contributes about 6.5% of gross domestic products (GDP) and 14.21% of total foreign exchange earnings in Bangladesh (DLS, 2017, Mustafa et al, 2020. Livestock plays a vital role in the traditional agriculture and largely subsistence economy of Bangladesh (Barman et al, 2017;Baset et al, 2003;Sarker et al, 2018;Rahman et al, 2002;Quddus and Rahman, 1998). The rural poor farmers largely depend on livestock (especially on small ruminants) for their survival (Ahmed, 1992).…”
Section: Introductionmentioning
confidence: 99%